Model Konseptual Kegagalan Operasional Adopsi Agile Project Management pada Industri Konstruksi Tradisional: Studi Pilot di Yogyakarta - Intan Permatasari; Iva Mindhayani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This research was conducted due to the high failure rate of Agile methods in construction projects in Yogyakarta, caused by clashes with traditional work systems. The objective is to identify the root causes of this problem and design a solution. Through a pilot study, data from expert questionnaires were analyzed quantitatively. The causal framework results indicate that failures are triggered by the interaction of regulatory, organizational, behavioral, technological, and financial barriers, which lead to schedule delays and rework. As a solution, a hybrid improvement framework is proposed, which includes: (1) hybrid governance and contracting that balances Waterfall (official documents/schedules) with Agile (team coordination), (2) incremental behavioral changes, (3) integration of digital monitoring tools, and (4) small-scale pilot evaluations prior to widespread implementation. This approach effectively bridges the rigid administrative demands with the need for speed in the field